2010
DOI: 10.1515/bmc.2010.006
|View full text |Cite
|
Sign up to set email alerts
|

Brain glutaminases

Abstract: Glutaminase is considered as the main glutamate producer enzyme in brain. Consequently, the enzyme is essential for both glutamatergic and gabaergic transmissions. Glutaminederived glutamate and ammonia, the products of glutaminase reaction, fulfill crucial roles in energy metabolism and in the biosynthesis of basic metabolites, such as GABA, proteins and glutathione. However, glutamate and ammonia are also hazardous compounds and danger lurks in their generation beyond normal physiological thresholds; hence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 116 publications
1
5
0
Order By: Relevance
“…Finally, we addressed the identification and quantitation of GA transcripts expressed by rat astrocytes. A real‐time RT‐PCR (qRT‐PCR) method was devised targeting the four GA isoforms so far reported to be expressed in mammalian tissues (Márquez et al, ; Martín‐Rufián et al, ). Total RNA was extracted from astrocytes isolated from rat cerebellum, a region where we found a significant population of cells positive for GA activity staining.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we addressed the identification and quantitation of GA transcripts expressed by rat astrocytes. A real‐time RT‐PCR (qRT‐PCR) method was devised targeting the four GA isoforms so far reported to be expressed in mammalian tissues (Márquez et al, ; Martín‐Rufián et al, ). Total RNA was extracted from astrocytes isolated from rat cerebellum, a region where we found a significant population of cells positive for GA activity staining.…”
Section: Resultsmentioning
confidence: 99%
“…This fact easily illustrates how astrocytes can modulate expression of GA isoforms, depending on the environmental conditions to which are they exposed, to maintain their energy and metabolic homeostasis. Mammalian KGA and GAB proteins possess different kinetic and regulatory properties; therefore, they reach full catalytic activity at different cellular concentrations of Gln, Glu, and Pi (Márquez et al, ). In this work, we have shown functional GA activity in the cytoplasm of discrete populations of hippocampal and cerebellar astrocytes, which can be ascribed to mitochondrial GA.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors reported that about 52% of the total human genes were subject to regulation by putative alternative promoters, and genes encoding signal-transduction related proteins were more likely to display alternative promoters. It is tempting to speculate that GLS2 transcripts may have this kind of regulatory mechanism in brain because the function of GAB and LGA transcripts might be associated to signaling or regulatory functions, besides their role as glutamate-producer enzymes [28], [43].…”
Section: Discussionmentioning
confidence: 99%
“…Doublelabeling revealed that GIP and GLS2 colocalized in astrocytes cell bodies and processes, including their perivascular end feet (Olalla et al, 2008). Considering the key role of astrocytes in cerebrovascular regulation (Iadecola and Nedergaard, 2007;Koehler et al, 2006), the GIP-GLS2 interaction might be implicated in this regulation throughout the synthesis of Glu, a vasoactive compound (Márquez et al, 2010).…”
Section: Ga In Mammalian Brainmentioning
confidence: 96%